Interventions to promote physical distancing behaviour during infectious disease pandemics or epidemics: A systematic review. (June 2022) - Epton, Tracy; Ghio, Daniela; Ballard, Lisa M.; Allen, Sarah F.; Kassianos, Angelos P.; Hewitt, Rachael; Swainston, Katherine; Fynn, Wendy Irene; Rowland, Vickie; Westbrook, Juliette; Jenkinson, Elizabeth; Morrow, Alison; et al.
Abstract: Objectives: Physical distancing, defined as keeping 1–2m apart when co-located, can prevent cases of droplet or aerosol transmitted infectious diseases such as SARS-CoV2. During the COVID-19 pandemic, distancing was a recommendation or a requirement in many countries. This systematic review aimed to determine which interventions and behavior change techniques (BCTs) are effective in promoting adherence to distancing and through which potential mechanisms of action (MOAs). Methods: Six databases were searched. The review included studies that were (a) conducted on humans, (b) reported physical distancing interventions, (c) included any comparator (e.g., pre-intervention versus post-intervention; randomized controlled trial), and (d) reported actual distancing or predictors of distancing behavior. Risk of bias was assessed using the Mixed Methods Appraisal Tool. BCTs and potential MoAs were identified in each intervention. Results: Six articles (with seven studies and 19 comparisons) indicated that distancing interventions could successfully change MoAs and behavior. Successful BCTs (MoAs) included feedback on behavior (e.g., motivation ); i nformation about health consequences, salience of health consequences (e.g., beliefs about consequences ), demonstration (e.g., beliefs about capabilities ), and restructuring the physical environment (e.g., environmental context and resources ). The most promising interventions were proximity buzzers, directional systems, and posters with loss-framed messages that demonstrated the behaviors. Conclusions: The evidence indicates several BCTs and potential MoAs that should be targeted in interventions and highlights gaps that should be the focus of future research. Highlights: Evaluates the effectiveness of interventions to promote distancing in pandemics. Six reports show that interventions can increase distancing. Key techniques: feedback, information about consequences, restructuring. Key delivery modes are posters and proximity buzzers. Further research is required to test more techniques and modes of delivery.